Activity of simian virus 40 late promoter elements in the absence of large T antigen: evidence for repression of late gene expression. - Alwine, J C (1986)
We used chloramphenicol acetyltransferase transient expression to examine the activity of the promoter elements of the simian virus 40 late promoter in the absence of large T antigen. Since the experiments were done in permissive CV-1 cells, these conditions mimic the state which exists early in the viral lytic cycle before the onset of replication and T-antigen-mediated trans activation. Our data, using deletion analysis, indicate that removal of the 21-base-pair (bp) repeat region causes as much as a 10-fold increase in activity of the late promoter elements. This result suggests that the 21-bp repeat sequences may be involved in repression of the late promoter elements during the early phase of the lytic infection. This is supported by competition analysis which indicates that increasing amounts of competitor containing only the 21-bp repeat region results in increased activity of the intact promoter. A model for the activity of the late promoter through the course of lytic infection is presented.